A phosphogypsum-based clsm material strength modifier and methods of use thereof

CN118307229BActive Publication Date: 2026-10-09KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410588143.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2026-10-09
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

[0004]鉴于上述不足,一种能够有效解决常规磷石膏基CLSM材料强度高、泌水率大的缺点,使其具有强度可控、泌水率低的优势的调节剂是目前行业内急需的

Benefits of technology

[0022] (1) By adding this regulator, the problems of high water bleeding rate and excessively high strength of conventional phosphogypsum-based CLSM materials can be solved, and it has the advantages of controllable strength and low water bleeding rate. As shown in Examples 1-4, the addition of this regulator controls the 28-day unconfined compressive strength of phosphogypsum-based CLSM materials to be between 0.3 and 2.1 MPa, and the water bleeding rate is <3%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a phosphogypsum-based CLSM material strength regulator and a use method thereof. The regulator is composed of 96-98% peat soil and 2-4% water reducing agent in mass ratio; the peat soil is required to have a loss on ignition w u ≥10%, a residual fiber content w f ≤1% and a pH value ≥6.0. The preparation and use method of the regulator are as follows: the water reducing agent is added into peat soil powder in proportion and stirred uniformly to obtain the regulator; the regulator is added in the preparation process of the phosphogypsum-based CLSM material; the adding amount of the regulator is controlled according to the following standards: when the loss on ignition w u of the peat soil is 10-30%, the regulator is added in 3 times of the cement content in the phosphogypsum-based CLSM material; when the loss on ignition w u of the peat soil is 30-60%, the regulator is added in 2 times; and when the loss on ignition w u of the peat soil is >60%, the regulator is added in 1 time. The regulator effectively solves the defects of high strength and high bleeding rate of the conventional phosphogypsum-based CLSM material, and makes the phosphogypsum-based CLSM material have the advantages of controllable strength and low bleeding rate, so that the phosphogypsum-based CLSM material is expected to be widely used in municipal pipeline backfill engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of strength modifier preparation and application methods, and in particular to a phosphogypsum-based CLSM material strength modifier and its application method. Background Technology

[0002] Controlled Low Strength Material (CLSM) is a new type of backfill material with high fluidity, capable of self-filling and forming a dense structure under its own weight with little or no vibration. Compared to traditional backfill soil or other loose materials, CLSM's excellent fluidity and self-compacting properties make it particularly suitable for special structures with high density, narrow spaces, and difficult access; it eliminates the need for vibration, rolling, and tamping processes, thereby reducing construction costs and shortening the construction period. In actual engineering projects, the strength of CLSM is generally controlled below 2.1 MPa to meet the requirements of repeated excavation and backfilling during the project's operation and maintenance phase.

[0003] Phosphogypsum (CaSO4·2H2O) is a solid waste generated during the production of phosphate fertilizers. my country adds approximately 80 million tons of phosphogypsum annually, with historical stockpiles exceeding 800 million tons. Conventional CLSM materials mainly consist of fine aggregates such as cement, fly ash, slag, and soil, water, and additives. The fine aggregate in phosphogypsum-based CLSM materials is primarily phosphogypsum. For every 1m³ of phosphogypsum prepared... 3 CLSM material can absorb nearly 0.8m³ of material. 3 Phosphogypsum is an effective way to realize the resource utilization of phosphogypsum. However, phosphogypsum particles are powder and fine sand, and it itself participates in the later reaction of the curing agent hydration products, generating crystals such as ettringite, which makes the filler dense and has high strength. Therefore, conventional phosphogypsum-based CLSM has a high bleeding rate and high strength; a high bleeding rate leads to large drying shrinkage and easy surface cracking; high strength makes it difficult to excavate later. Adjusting the water-cement ratio can change the unconfined compressive strength of phosphogypsum-based CLSM materials; reducing the cement content reduces the strength; however, if the cement content is reduced, the setting time may not meet the requirements, and the bleeding rate will increase, and the volume shrinkage after setting will be significant.

[0004] Given the above shortcomings, a regulator that can effectively solve the problems of high strength and high water bleeding rate of conventional phosphogypsum-based CLSM materials, and give them the advantages of controllable strength and low water bleeding rate, is urgently needed in the industry. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to provide a strength modifier for phosphogypsum-based CLSM materials and its application method. This invention enables conventional phosphogypsum-based CLSM materials to maintain other performance requirements while also possessing advantages such as controllable strength and low bleeding rate, making them better suited for municipal pipeline backfilling projects, facilitating repeated excavation in the future, and saving project costs. This invention is achieved through the following technical means:

[0006] This invention provides a phosphogypsum-based CLSM material strength modifier, comprising the following raw materials by mass percentage:

[0007] 96-98% peat moss and 2-4% water-reducing agent; wherein:

[0008] The peat soil is required to have a loss on ignition (w). u ≥10%, residual fiber content w f ≤1%, pH value ≥6.0;

[0009] The water-reducing agent mentioned is a polycarboxylate water-reducing agent.

[0010] Organic matter in peat moss is adsorbed onto the surface of cement particles, partially hindering their hydration. Meanwhile, the large specific surface area and double-layered porous structure of humus greatly increase its water adsorption capacity, reducing the material's water leakage.

[0011] The present invention also provides a method for using the above-mentioned phosphogypsum-based CLSM material strength modifier, comprising:

[0012] (1) Peat soil is naturally dried, crushed, and sieved to obtain peat soil powder with a particle size of less than 1 mm for later use.

[0013] (2) Add water-reducing agent to peat powder and stir evenly to obtain regulator;

[0014] (3) This regulator is added during the preparation of phosphogypsum-based CLSM materials.

[0015] Further, the loss on ignition w of the peat soil in step (1) u ≥10%, residual fiber content w f ≤1%, pH value ≥6.0.

[0016] Further, in step (2), a water-reducing agent is added to the peat powder, with the peat accounting for 96-98% and the water-reducing agent accounting for 2-4% by mass percentage.

[0017] Furthermore, the amount of this regulator added in step (3) is controlled according to the following standards:

[0018] The loss on ignition of the peat soil w uWhen the content is 10-30%, add it at 3 times the mass of cement in the phosphogypsum-based CLSM material;

[0019] The loss on ignition of the peat soil w u When the content is 30-60%, add twice the amount of cement in the phosphogypsum-based CLSM material;

[0020] The loss on ignition of the peat soil w u When the content is >60%, add it at 1 times the mass of cement in the phosphogypsum-based CLSM material.

[0021] The beneficial effects of this invention are:

[0022] (1) By adding this regulator, the problems of high water bleeding rate and excessively high strength of conventional phosphogypsum-based CLSM materials can be solved, and it has the advantages of controllable strength and low water bleeding rate. As shown in Examples 1-4, the addition of this regulator controls the 28-day unconfined compressive strength of phosphogypsum-based CLSM materials to be between 0.3 and 2.1 MPa, and the water bleeding rate is <3%.

[0023] (2) The regulator of the present invention is simple to produce and prepare, has a simple implementation process, is inexpensive, and is easy to promote and apply in industrial applications. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1

[0026] A strength modifier for phosphogypsum-based CLSM materials, comprising the following raw materials in weight percentages:

[0027] The peat moss contains 96-98% peat and 2-4% water-reducing agent by mass; wherein the loss on ignition of the peat moss is w. u ≥10%, residual fiber content w f ≤1%, pH value ≥6.0.

[0028] The water-reducing agent is a polycarboxylate water-reducing agent.

[0029] The method of using the phosphogypsum-based CLSM material strength modifier includes:

[0030] (1) Peat soil is naturally dried, crushed, and sieved to obtain peat soil powder with a particle size of less than 1 mm for later use.

[0031] (2) Add water-reducing agent to peat powder and stir evenly to obtain regulator;

[0032] (3) This regulator is added during the preparation of phosphogypsum-based CLSM materials.

[0033] Further, the loss on ignition w of the peat soil in step (1) u =13.65%, residual fiber content w f =0.8%, pH value =6.8.

[0034] Furthermore, in step (2), the water-reducing agent is added to the peat powder, with the peat accounting for 98% and the water-reducing agent accounting for 2% by mass percentage.

[0035] Furthermore, the amount of this regulator added in step (3) is controlled according to the following standards:

[0036] The loss on ignition of the peat soil w u When the content is 10-30%, add it at 3 times the mass of cement in the phosphogypsum-based CLSM material;

[0037] The loss on ignition of the peat soil w u When the content is 30-60%, add twice the amount of cement in the phosphogypsum-based CLSM material;

[0038] The loss on ignition of the peat soil w u When the content is >60%, add it at 1 times the mass of cement in the phosphogypsum-based CLSM material.

[0039] Further, in step (3), the phosphogypsum-based CLSM material is prepared by mass percentage as follows: cement accounts for 12%, fly ash accounts for 8%, phosphogypsum accounts for 30%, and regulator accounts for 50%.

[0040] The engineering properties of the specimens prepared according to the mix proportion determined in this embodiment, including flowability, bleeding rate, setting time, and strength, were tested. The measured flowability was 163 mm; the final bleeding rate was 2.67%; the setting time was 18.5 h; and the 28-day unconfined compressive strength was 0.875 MPa.

[0041] Example 2

[0042] A strength modifier for phosphogypsum-based CLSM materials, comprising the following raw materials in weight percentages:

[0043] The peat moss contains 96-98% peat and 2-4% water-reducing agent by mass; wherein the loss on ignition of the peat moss is w. u ≥10%, residual fiber content w f ≤1%, pH value ≥6.0.

[0044] The water-reducing agent is a polycarboxylate water-reducing agent.

[0045] The method of using the phosphogypsum-based CLSM material strength modifier includes:

[0046] (1) Peat soil is naturally dried, crushed, and sieved to obtain peat soil powder with a particle size of less than 1 mm for later use.

[0047] (2) Add water-reducing agent to peat powder and stir evenly to obtain regulator;

[0048] (3) This regulator is added during the preparation of phosphogypsum-based CLSM materials.

[0049] Further, the loss on ignition w of the peat soil in step (1) u =37.91%, residual fiber content w f =0.8%, pH value =6.5.

[0050] Furthermore, in step (2), the water-reducing agent is added to the peat powder, with the peat accounting for 97% and the water-reducing agent accounting for 3% by mass percentage.

[0051] Furthermore, the amount of this regulator added in step (3) is controlled according to the following standards:

[0052] The loss on ignition of the peat soil w u When the content is 10-30%, add it at 3 times the mass of cement in the phosphogypsum-based CLSM material;

[0053] The loss on ignition of the peat soil w u When the content is 30-60%, add twice the amount of cement in the phosphogypsum-based CLSM material;

[0054] The loss on ignition of the peat soil w u When the content is >60%, add it at 1 times the mass of cement in the phosphogypsum-based CLSM material.

[0055] Further, in step (3), the phosphogypsum-based CLSM material is prepared by mass percentage, with cement accounting for 12%, fly ash accounting for 8%, phosphogypsum accounting for 40%, and regulator accounting for 40%.

[0056] The engineering properties of the specimens prepared according to the mix proportion determined in this embodiment, including flowability, bleeding rate, setting time, and strength, were tested. The measured flowability was 163 mm; the final bleeding rate was 2.12%; the setting time was 20.4 h; and the 28-day unconfined compressive strength was 0.518 MPa.

[0057] Example 3

[0058] A strength modifier for phosphogypsum-based CLSM materials, comprising the following raw materials in weight percentages:

[0059] The peat moss contains 96-98% peat and 2-4% water-reducing agent by mass; wherein the loss on ignition of the peat moss is w. u ≥10%, residual fiber content w f ≤1%, pH value ≥6.0.

[0060] The water-reducing agent is a polycarboxylate water-reducing agent.

[0061] The method of using the phosphogypsum-based CLSM material strength modifier includes:

[0062] (1) Peat soil is naturally dried, crushed, and sieved to obtain peat soil powder with a particle size of less than 1 mm for later use.

[0063] (2) Add water-reducing agent to peat powder and stir evenly to obtain regulator;

[0064] (3) This regulator is added during the preparation of phosphogypsum-based CLSM materials.

[0065] Further, the loss on ignition w of the peat soil in step (1) u =53.30%, residual fiber content w f =0.6%, pH value =6.2.

[0066] Furthermore, in step (2), the water-reducing agent is added to the peat powder, with the peat accounting for 97% and the water-reducing agent accounting for 3% by mass percentage.

[0067] Furthermore, the amount of this regulator added in step (3) is controlled according to the following standards:

[0068] The loss on ignition of the peat soil w u When the content is 10-30%, add it at 3 times the mass of cement in the phosphogypsum-based CLSM material;

[0069] The loss on ignition of the peat soil w u When the content is 30-60%, add twice the amount of cement in the phosphogypsum-based CLSM material;

[0070] The loss on ignition of the peat soil w u When the content is >60%, add it at 1 times the mass of cement in the phosphogypsum-based CLSM material.

[0071] Further, in step (3), the phosphogypsum-based CLSM material is prepared by mass percentage, with cement accounting for 12%, fly ash accounting for 8%, phosphogypsum accounting for 40%, and regulator accounting for 40%.

[0072] The engineering properties of the specimens prepared according to the mix proportion determined in this embodiment, including flowability, bleeding rate, setting time, and strength, were tested. The measured flowability was 166 mm; the final bleeding rate was 1.36%; the setting time was 22.1 h; and the 28-day unconfined compressive strength was 0.388 MPa.

[0073] Example 4

[0074] A strength modifier for phosphogypsum-based CLSM materials, comprising the following raw materials in weight percentages:

[0075] The peat moss contains 96-98% peat and 2-4% water-reducing agent by mass; wherein the loss on ignition of the peat moss is w. u ≥10%, residual fiber content w f ≤1%, pH value ≥6.0.

[0076] The water-reducing agent is a polycarboxylate water-reducing agent.

[0077] The method of using the phosphogypsum-based CLSM material strength modifier includes:

[0078] (1) Peat soil is naturally dried, crushed, and sieved to obtain peat soil powder with a particle size of less than 1 mm for later use.

[0079] (2) Add water-reducing agent to peat powder and stir evenly to obtain regulator;

[0080] (3) This regulator is added during the preparation of phosphogypsum-based CLSM materials.

[0081] Further, the loss on ignition w of the peat soil in step (1) u =70.21%, residual fiber content w f =0.5%, pH value =6.1.

[0082] Furthermore, in step (2), the water-reducing agent is added to the peat powder, with the peat accounting for 96% and the water-reducing agent accounting for 4% by mass percentage.

[0083] Furthermore, the amount of this regulator added in step (3) is controlled according to the following standards:

[0084] The loss on ignition of the peat soil w u When the content is 10-30%, add it at 3 times the mass of cement in the phosphogypsum-based CLSM material;

[0085] The loss on ignition of the peat soil w u When the content is 30-60%, add twice the amount of cement in the phosphogypsum-based CLSM material;

[0086] The loss on ignition of the peat soil w uWhen the content is >60%, add it at 1 times the mass of cement in the phosphogypsum-based CLSM material.

[0087] Further, in step (3), the phosphogypsum-based CLSM material is prepared by mass percentage as follows: cement accounts for 12%, fly ash accounts for 8%, phosphogypsum accounts for 60%, and regulator accounts for 20%.

[0088] The engineering properties of the specimens prepared according to the mix proportion determined in this embodiment, including flowability, bleeding rate, setting time, and strength, were tested. The measured flowability was 162 mm; the final bleeding rate was 2.06%; the setting time was 21.5 h; and the 28-day unconfined compressive strength was 0.476 MPa.

[0089] Comparative Example 1

[0090] In this comparative example, no modifier was added during the preparation of the phosphogypsum-based CLSM material, and its components included cement, fly ash, and phosphogypsum.

[0091] Furthermore, the phosphogypsum-based CLSM material is prepared by mass percentage, with cement accounting for 12%, fly ash accounting for 8%, and phosphogypsum accounting for 80%.

[0092] The engineering properties of the specimens prepared by determining the mix proportion in this comparative example, including flowability, bleeding rate, setting time, and strength, were tested. The measured flowability was 162 mm; the final bleeding rate was 21.02%; the setting time was 20.4 h; and the 28-day unconfined compressive strength was 1.533 MPa.

[0093] Experimental Example 1

[0094] The results of the water bleeding rate and 28-day unconfined compressive strength of the specimens prepared in Examples 1-4 and Comparative Example 1 are shown in Table 1:

[0095] Table 1

[0096] Example 1 2.67 0.875 Example 1 2.12 0.518 Example 1 1.36 0.388 Example 1 2.06 0.476 Comparative Example 1 21.02 1.533

[0097] As shown in Table 1, the specimens prepared in Examples 1-4 exhibited better performance than the specimen prepared in Comparative Example 1 in terms of both bleeding rate and 28-day unconfined compressive strength. This indicates that the modifier used played a significant role in regulating the strength and bleeding rate of the phosphogypsum-based CLSM material. Furthermore, the performance parameters of the specimens prepared in Examples 1-4 also met engineering requirements. Therefore, the addition of this modifier makes the strength of the phosphogypsum-based CLSM material controllable, significantly reduces the bleeding rate, and makes it more suitable for municipal pipeline backfilling projects.

[0098] Reaction mechanism

[0099] The organic matter in peat moss is mainly humus, which has the characteristics of a porous amorphous colloidal substance and a strong water adsorption and retention capacity. After peat moss and fluidized slurry are thoroughly mixed, the humus can enhance the water retention of the slurry, thereby reducing the bleeding rate. In addition, the acidity of humus can neutralize the alkaline environment during cement hydration, adsorb calcium and aluminum ions produced during cement hydration, reduce hydration products, and further reduce the later strength. In the later stage of curing of phosphogypsum-based CLSM materials, the humus in peat moss reacts with the volcanic ash involved in phosphogypsum to produce ettringite, which fills the pores in the material and increases stiffness and strength. The addition of peat moss can significantly reduce unconfined compressive strength and bleeding rate. In addition, polycarboxylate superplasticizer (PCE) can reduce the water content of the mixture by increasing electrostatic force and steric hindrance, improving fluidity, and further reducing the bleeding rate. Therefore, adding peat and polycarboxylate superplasticizer (PCE) as modifiers to phosphogypsum-based CLSM materials can not only control the unconfined compressive strength but also ensure a low bleeding rate, which is of great significance for applications such as municipal pipeline backfilling projects.

[0100] Table 2 CLSM Flowability Classification

[0101] low fluidity 100~150 Backfilling projects for large-scale pipe trenches, roadbeds, etc. General fluidity 150~200 General backfilling projects High fluidity >200 Backfilling projects with narrow operating spaces or dead corners

[0102] Although the flowability of controllable low-strength materials increases with increasing bleeding rate within a certain range, excessively high bleeding rates are detrimental to their strength. Excessive bleeding rates can lead to severe uneven settlement of the controllable low-strength material, affecting backfill quality and potentially forming a weak layer with insufficient strength to support vehicle loads. Related research indicates that in engineering practice, a bleeding rate of less than 3% for controllable low-strength materials is feasible. Therefore, the optimal bleeding rate for prepared controllable low-strength materials should be ≤3%.

[0103] The hardening time of controllable low-strength materials is generally required to be within 24 hours, mainly for rapid use in engineering projects.

[0104] Although the upper limit of the compressive strength of controllable low-strength materials is 8.3 MPa, it is more reasonable to control the upper limit of strength at 2.1 MPa to facilitate the re-excavation process in later construction. At the same time, the compressive strength of high-quality soil filler is 0.3 to 0.7 MPa, so the 28-day strength of the prepared controllable low-strength materials should be controlled at 0.3 to 0.7 MPa.

[0105] Based on the test results of Examples 1 to 4, it can be seen that the flowability of the CLSM obtained by the present invention is greater than 150 mm, which is a general flowability filling material suitable for general backfilling projects; the bleeding rate is within 3%, indicating that the CLSM has good stability; the hardening time is within 24 hours, which is convenient for rapid use in projects; the 28-day unconfined compressive strength is 0.3 to 0.7 MPa, which is convenient for the excavation requirements of later construction.

[0106] As can be seen from the above examples, the solution provided by the present invention can adjust the strength of CLSM that meets the engineering requirements by means of a regulator while ensuring the control index of phosphogypsum-based CLSM. This keeps the 28-day unconfined compressive strength of phosphogypsum-based CLSM within a controllable range, while reducing the bleeding rate and avoiding significant settlement. It is expected to be widely used in municipal pipeline backfilling projects.

[0107] The above description represents only the preferred embodiment of the present invention. It should be noted that, without departing from the technical principles of the present invention, those skilled in the art can make several improvements and modifications. These improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A phosphogypsum-based CLSM material strength modifier, comprising the following raw materials in the indicated mass percentages: The mixture contains 96-98% peat moss and 2-4% water-reducing agent by weight; wherein: The loss on ignition of the peat soil w u ≥10%, residual fiber content w f ≤1%, pH value ≥6.0; The water-reducing agent is a polycarboxylate water-reducing agent.

2. A method of using the phosphogypsum-based CLSM material strength modifier according to claim 1, comprising: (1) Peat soil is naturally dried, crushed, and sieved to obtain peat soil powder with a particle size of less than 1 mm for later use. (2) Add water-reducing agent to peat powder and stir evenly to obtain regulator; (3) This regulator is added during the preparation of phosphogypsum-based CLSM materials; Wherein: the loss on ignition of peat soil w in step (1) u ≥10%, residual fiber content w f ≤1%, pH value ≥6.

0.

3. The method of use according to claim 2, wherein: The loss on ignition of the peat soil w u When the content is 10-30%, add it at 3 times the mass of cement in the phosphogypsum-based CLSM material.

4. The method of use according to claim 2, wherein: The loss on ignition of the peat soil w u When the content is 30-60%, add twice the amount of cement in the phosphogypsum-based CLSM material.

5. The method of use according to claim 2, wherein: The loss on ignition of the peat soil w u When the content is >60%, add it at 1 times the mass of cement in the phosphogypsum-based CLSM material.

Citation Information

Patent Citations

  • Novel controllable low-strength material and preparation method thereof

    CN113548852A